Engineered substrates with imprinted cell-like topographies induce direct differentiation of adipose-derived mesenchymal stem cells into Schwann cells - Mehrdad Moosazadeh Moghaddam; Shahin Bonakdar; Mohammad Ali Shokrgozar; Arash Zaminy; Hojatollah Vali; Shahab Faghihi (Artificial Cells, Nanomedicine, and Biotechnology)
Differentiation of stem cells to Schwann is considered efficient way for nerve regeneration since the sources of human Schwann cells are limited for clinical application. It is demonstrated that mimicking micromechanical forces or micro/nanotopographical environments that stem cells are experienced in vivo could control their fate. Here, the potency of substrates with imprinted cell-like topographies for direct differentiation of adipose-derived mesenchymal stem cells (ADSCs) into Schwann cells (SCs) is reported. For the preparation of substrates with imprinted SC-Like topographies, SCs are isolated from the sciatic nerve, grown, fixed, and then SC morphologies are transferred to polydimethylsiloxane (PDMS) substrates by mold casting. Subsequently, mesenchymal stem cells (MSCs) are seeded on the SC-imprinted substrates and their differentiation to SCs is evaluated by immunocytochemistry, real-time PCR, and western blotting. Analysis of morphology and expression of SC-specific markers show that MSCs cultured on the imprinted substrates have the typical SC-like morphology and express SC-specific markers including S100b, p75NTR, and Sox10. It is believed that specific cell-like topographies and related micromechanical cues can be sufficient for direct differentiation of ADSCs into Schwann cells by cell-imprinting method as a physical technique.